Dynamics in the regulatory genome - Georgiades, E (2022)
The way in which DNA is uniquely folded in the nucleus into specific conformations enables and/or reflects cell-type specific interactions of active cis-regulatory elements, namely promoters and enhancers, to regulate specific programs of gene expression. The cohesin protein complex is a key player in the dynamic organisation of genome folding, orchestrating chromatin looping through a process known as loop extrusion. How this process is directed in a cell-type specific manner is currently unknown. A widely accepted hypothesis is that cohesin is recruited to active cis-regulatory elements, however current methods are unable to assay the dynamic nature of cohesin loading onto the chromatin. To address this, in this thesis I have developed inducible cellular models that enable cohesin to be tracked in a dynamic manner, in an attempt to answer this question.